Exploring the General Knowledge of Islamic Finance Principles: A Factor Analysis Study Among College Students - Lelis, Christhoffer; Muega, Neil Patrick S.; Caballero II, Jose Karlo T. (International Journal of Finance Research, 2023)
This study explored the foundational constructs of general knowledge concerning the principles of Islamic Finance, with a specific focus on college students majoring in Business, Finance, and Accountancy. Employing a combination of exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), the research identified and validated three distinct factors shaping this knowledge domain. The first factor, named "Risk Tolerance and Permissible Transactions," looks at how well students understand financial risk and which transactions are allowed in Islamic finance. The second, "Shari'ah Foundation and Transparency," highlights the importance of Shari'ah principles and transparency in financial dealings. The third, "Riba Prohibition and Ethical Finance," strongly emphasizes the ban on Riba (interest) and unethical financial practices in Islamic finance. These factor names were chosen carefully to represent the main ideas in each category. Overall, this research contributes by creating a validated objective knowledge scale for Islamic Finance knowledge among students in Business, Finance, and Accountancy programs. Keywords: Islamic Finance, Knowledge Assessment, Factor Analysis, College Students, Financial Literacy